Experimental investigation of current forces on a square caisson with small aspect ratios during the sinking process. Issue 6 (2nd November 2022) - Yang, Hanbin; Hou, Shengjun; Yang, Wanli; Li, Sijing; Hou, Hailin; Li, Qiao
ABSTRACT: The study of flow around a square caisson considering the combined effects of free surface, free end and bottom boundary is limited. Experiments were performed in this study to investigate the characteristics of current forces on a square caisson model considering the combined effects of free surface, free end and bottom boundary. Results show that the drag coefficient and the root mean square coefficient of transverse force generally increase with aspect ratio ( AR ), and significantly increase at the instant when the free end disappears. The bottom boundary decreases the values of root mean square coefficients of drag force and vertical force. The drag coefficient decreases with incident angle ( α ) when 0 ∘ ≤ α ≤ 15 ∘, but increases with α when 15 ∘ ≤ α ≤ 45 ∘ . The trim and squat phenomenon caused by shallow water effect when the caisson is nearly touching the riverbed (seabed) during the sinking process should receive extra attention in practice.